A ASSESSMENT OF/AS/FOR LEARNING: ANALISIS PRINSIP-PRINSIP DAN FILOSOFI PENILAIAN SERTA IMPLEMENTASINYA DALAM PEMBELAJARAN KIMIA : ASSESSMENT OF/AS/FOR LEARNING: ANALISIS PRINSIP-PRINSIP DAN FILOSOFI PENILAIAN SERTA IMPLEMENTASINYA DALAM PEMBELAJARAN KIMIA (HISKIA : Jurnal Ilmu Kimia & Pendidikan Kimia, 2025)
The assessment system is one of the important aspects that contribute to improving the quality of education in general. Therefore, it is important to review the principles and philosophy of assessment, the implementation of assessment of, as, and for learning, the role of technology that increases the effectiveness of assessment, especially in chemistry learning. The method used in this review is narrative literature review. This review produces several important points, namely first, assessment in chemistry learning needs to be aligned with learning objectives, use of various methods, and provide constructive feedback that can increase student understanding and engagement. Second, the philosophy of assessment emphasizes the development of effective evaluation instruments, technology integration and results-based approaches that support meaningful and in-depth learning. Third, good assessment needs to involve three main approaches: feedback and continuous improvement during the learning process (Assessment for Learning/AfL), assessing the final learning outcomes through exams and summative tasks (Assessment of Learning/AoL), and involving students in the assessment process to reflect and improve understanding (Assessment as Learning/AaL). Fourth, the development of information and communication technology (ICT) has increased the effectiveness of assessment in chemistry education by providing a variety of innovative tools and methods, such as computer-based assessment.
Keywords: Assessment of/as/for Learning; Assessment philosophy; Chemistry learning